(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Factors and indicators of the process of desertification of the territory of Armenia are examined; protective measures, which can weaken this negative process, are marked. It’s concluded that the process of desertification in the territory of Armenia increased during the last 15-20 years in connection with the activation of geodynamic situation in the region and with unfavorable social- economic conditions as well as sharp changing of dangerous hydrometeorological phenomena and increase of their frequency, connected with the planetary changes of climate.